25(OH)D Inadequacy Has Different Pathway with VEGF in Increases the Risk of Severe Preeclampsia - Hanifa Erlin Damayanti; Aditiawarman Aditiawarman (Universitas Airlangga, 2015)
Objectives: To identify in vivo correlation between 25(OH)D and VEGF in severe preeclampsia.Materials and Methods: A case control, cross sectional study of 36 pregnant women which consist of 18 patients with preeclampsia and 18 patients as control with gestational age-matched. We perform 25(OH)D serum examination by chemiluminescent immunoassay (CLIA) and VEGF serum examination by sandwich ELISA to all patients.Results: All patients are in 25(OH)D insufficiency and deficiency state. Both maternal 25(OH)D and VEGF levels were inversely associated with the risk of preeclampsia (both P<0.05). There is no correlation between 25(OH)D serum level and VEGF serum level (P=0,629).Conclusion: Maternal vitamin D deficiency is associated with increased preeclampsia risk. However, our data do not support the hypothesis that the association between vitamin D deficiency and preeclampsia is mediated by impaired level of VEGF.